THE ANALYSIS OF SELECTION AND TRAINING MODEL IN EFFORTS TO INCREASE EMPLOYEE PERFORMANCE PT. ARZURO HR PERFORMANCE - Duddy Dinantara, Mohamad (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
The study conducted at PT Arzuro Kinerja SDM aims to prove empirically the effect of selection and training on employee performance, both partially and simultaneously. The method used in the study was descriptive quantitative, with multiple regression analysis. The independent variable of the study uses Selection (variable X1) and Training (variable X2), while the dependent variable of the study uses Employee Performance (variable Y). The sample used in the study was 100 saturated samples, which were taken directly through a questionnaire of 100 respondents. Hypothesis testing shows that selection and training have significant positive effect on employee performance, both partially and simultaneously. The regression model of the research results Y = 0.147+ 0.864X1 + 0.158X2.